Cytomegalovirus infection in Guillain-Barré syndrome: a retrospective study in Brazil - Mario Emilio Teixeira Dourado Junior; Bruno Fernandes de Sousa; Nathaly M. Coelho da Costa; Selma Maria Bezerra Jeronimo (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Guillain-Barré syndrome (GBS) is currently the most common cause of acute flaccid paralysis worldwide. Risk factors for GBS include previous viral or bacterial infections or vaccination. Recently, an outbreak of Zika virus led to an outbreak of GBS in Latin America, mostly in Brazil, concomitant to continuous circulation of dengue virus serotypes. However, there is no study about cytomegalovirus (CMV) infection as a risk for GBS in Brazil. Objectives: In this study, we report a series of cases of GBS with the aim of determining the prevalence of CMV and the characteristics associated with the infection. Methods: A cohort of 111 GBS cases diagnosed between 2011 and 2017 in Natal, northeastern Brazil, was studied. Presence of CMV IgM antibodies was determined by means of electrochemiluminescence. The analysis was performed considering CMV infection status and the clinical outcome. Results: We found seroprevalence of 15.3% (n = 17) for CMV. CMV patients were younger (26 vs. 40; p = 0.016), with no apparent gastrointestinal (p = 0.762) or upper respiratory infections (p = 0.779) or sensory loss (p = 0.03). They presented more often with a classic GBS sensorimotor variant (p = 0.02) and with a demyelinating pattern in electrophysiological studies (p < 0.001). Conclusion: In Brazil, the clinical-epidemiological profile of GBS associated with CMV infection is similar to that described in other countries. Better understanding of the relationship between infectious processes and GBS is a key component of the research agenda and assistance strategy for global health initiatives relating to peripheral neuropathic conditions.